Plastics recycling as a future business opportunity - Recyclingplas Conference on Plastics Recycling as a Future Business Opportunity (4th : 1989 : Washington, D.C.); Plastics Institute of America, Inc. (Lancester, PA : Technomic Pub., 1989)
22